Attitudes of health professionals and primary school staff towards the separation of children from families and foster care - Vidović Vondra, Suzana (Array, 2020)
In Croatia, the process of deinstitutionalization of childcare is underway, and it should increase the placement of children in non-institutional forms of care such as foster care. The aim of the study was to examine attitudes towards foster care and child separation among school and adult mental health professionals. The sample consisted of 159 respondents (employees of elementary schools in Kutina, Popovača and Velika Ludina and employees of the Neuropsychiatric Hospital “Dr. Ivan Barbot” in Popovača). The survey covered all relevant sociodemographic variables, and the Scale of Attitudes Towards Separation of Children from Family and the Attitudes Towards Foster Care Scale were used to examine attitudes [Kamenov, Sladovic Franz & Ajdukovic, 2005]. In the sample examined, attitudes to foster care and separation are slightly positive, indicating that there is plenty of room for activities aimed at empowering these views. If further attitudes are to be strengthened, therefore the population of potential future foster parents is also expected to expand. It is important to highlight the role of healthcare professionals involved in the mental health care of foster children and to consider their role in modifying general attitudes towards foster care for children and their role in building an optimal foster care system.